Tick-Borne Flavivirus Inhibits Sphingomyelinase (IsSMase), a Venomous Spider Ortholog to Increase Sphingomyelin Lipid Levels for Its Survival in Ixodes scapularis Ticks - Regmi, Pravesh; Khanal, Supreet; Neelakanta, Girish; Sultana, Hameeda (Frontiers in Cellular and Infection Microbiology, 2020)
Our previous study showed that cells from medically important arthropods, such as ticks, secrete extracellular vesicles (EVs) including exosomes that mediate transmission of flavivirus RNA and proteins to the human cells. Understanding the molecular determinants and mechanism(s) of arthropod-borne flavivirus transmission via exosome biogenesis is very important. In this current study, we showed that in the presence of tick-borne Langat Virus (LGTV; a member of tick-borne encephalitis virus complex), the expression of arthropod IsSMase, a sphingomyelinase D (SMase D) that catalyzes the hydrolytic cleavage of substrates like sphingomyelin (SM) lipids, was significantly reduced in both Ixodes scapularis ticks (in vivo) and in tick cells (in vitro). The IsSMase reduced levels correlated with down-regulation of its activity upon LGTV replication in tick cells. Our data show that LGTV-mediated suppression of IsSMase allowed accumulation of SM lipid levels that supported membrane-associated viral replication and exosome biogenesis. Inhibition of viral loads and SM lipid built up upon GW4869 inhibitor treatment reversed the IsSMase levels and restored its activity. Our results suggest an important role for this spider venomous ortholog IsSMase in regulating viral replication associated with membrane-bound SM lipids in ticks. In summary, our study not only suggests a novel role for arthropod IsSMase in tick-LGTV interactions but also provides new insights into its important function in vector defense mechanism(s) against tick-borne virus infection and in anti-viral pathway(s).